2022
DOI: 10.2196/33696
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Mobile App Engagement on Mental Health Outcomes: Secondary Analysis of the Unwinding Anxiety Program

Abstract: Background App-based interventions provide a promising avenue for mitigating the burden on mental health services by complimenting therapist-led treatments for anxiety. However, it remains unclear how specific systems’ use of app features may be associated with changes in mental health outcomes (eg, anxiety and worry). Objective This study was a secondary analysis of engagement data from a stage 1 randomized controlled trial testing the impact of the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
“…The following observations only occurred once in the literature: decrease in anger [26], decrease in decision conflict [30], decrease in decision regret [30], decreased digestive disturbance [26], decreased pain [26], increased medication adherence [41], and the intervention had no effect on self-efficacy [34]. [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56] 19 Reduced anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 3 more Smart Citations